2020
DOI: 10.1177/0960327120911438
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effect of gastrodin in methamphetamine-induced apoptosis through regulating cAMP/PKA/CREB pathway in cortical neuron

Abstract: Objective: Methamphetamine (MA) abuse induces neurotoxicity and causes neuronal cell apoptosis. Gastrodin is a traditional Chinese herbal medicine used for the treatment of nerve injuries, spinal cord injuries, and some central nervous system diseases as well. The present study investigated the neuroprotective effects of gastrodin against MA-induced neurotoxicity in neuronal cells and its potential protective mechanism. Methods: The primary cortex neuronal culture was divided into four groups (control group, M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 30 publications
(29 reference statements)
1
11
0
Order By: Relevance
“…Conversely, Sigmar1 genetic ablation attenuates CREB expression and pCREBSer133 expression. Our findings are agreement with studies that demonstrated that chronic METH treatment in rats (4 mg/kg, IP, 2 weeks) resulted in decreased CREB/pCREB immunostaining in the neuronal nuclei of striatum 60 and decreased pCREB expression in METH-treated cultured primary cortical neurons 61 . Similarly, both acute and repeated METH exposure (5 mg/kg, IP) suppresses the striatal expression of CREB mRNA 62 .…”
Section: Discussionsupporting
confidence: 93%
“…Conversely, Sigmar1 genetic ablation attenuates CREB expression and pCREBSer133 expression. Our findings are agreement with studies that demonstrated that chronic METH treatment in rats (4 mg/kg, IP, 2 weeks) resulted in decreased CREB/pCREB immunostaining in the neuronal nuclei of striatum 60 and decreased pCREB expression in METH-treated cultured primary cortical neurons 61 . Similarly, both acute and repeated METH exposure (5 mg/kg, IP) suppresses the striatal expression of CREB mRNA 62 .…”
Section: Discussionsupporting
confidence: 93%
“…The insufficient expression of ADCY by the D-gal induction can lead the reduction of the cAMP expression. The attenuated expression of the cAMP may further lead to the protein kinase (PKA) inactivation, following which to inhibit the expression of phosphorylated cAMP response element binding protein (CREB) [ 65 ]. The CREB is a molecular switch that is the core component of long-term memory.…”
Section: Discussionmentioning
confidence: 99%
“…PKA, p-PKA, CREB, and p-CREB are highly expressed in different brain regions of MA-induced conditioned place preference (CPP) rats and in SH-SY5Y cells, but can be inhibited by gastrodin (Yang et al, 2020b). The cAMP/PKA/CREB pathway is also involved in the apoptosis of cortical neurons induced by MA, but can be regulated by the neuroprotective effects of gastrodin (Ma et al, 2020). In this study, the expression levels of PKA, p-PKA, CREB, and p-CREB decreased following CBD pretreatment, indicating that CBD may attenuate myocardial in ammation and cardiac pathology by mediating the PKA/CREB signaling pathway.…”
Section: Discussionmentioning
confidence: 99%